Karya Naṣā’iḥ al-‘Ibād oleh Nawawi al-Bantani dan Sirāj al-Ṭālibīn oleh Ihsan Muhammad Dahlan al-Jampasi al-Kediri: Kajian Perbandingan Terhadap Metode Penulisan Hadith: The Works of Naṣā’iḥ al-‘Ibād by Nawawi al-Bantani and Sirāj al-Ṭālibīn by Ihsan Muhammad Dahlan al-Jampasi al-Kediri: A Comparative Research on the Methods of Writing the Hadith - Kirin, Arwansyah; Ismail, Faisal Husen; Borham, Abd Shakor (Jurnal Usuluddin, 2020)
The book of Naṣā’iḥ al-‘Ibād by Nawawi al-Bantani and Sirāj al-Ṭālibīn by Ihsan al-Jampasi are one of the main references used in the Nusantara Archipelago on Islamic knowledge relating to religious advices and tasawuf. Both books contain many hadiths and yet they are not stated about the position of the hadith. Therefore, this study aims to identify the methods used in writing the hadith by Nawawi al-Bantani and Ihsan al-Jampasi in the book of Naṣā’iḥ al-‘Ibād and Sirāj al-Ṭālibīn. This study also compares the methods adopted by the two books in the writing of hadith. This is done to find the similarities and differences between the two methods. The method for this study is qualitative, through the use of library research and analysis design of the contents in the books of Naṣā’iḥ al-‘Ibād and Sirāj al-Ṭālibīn. This study had found that, there exists similarities in the method of writing the hadith in the book of Naṣā’iḥ al-‘Ibād and Sirāj al-Ṭālibīn, which is in the writing of hadith without a sanad and only stating the mukhrij of the hadith. Furthermore, the two books had also used lafaz (sighat) Qala’ at the beginning of the hadith. Meanwhile, the differences that had been found in this study is such that Nawawi al-Bantani writes the hadith without a sanad by adding the rāwī a‘lā at the stage of tabi’in and sahabah. Nawawi al-Bantani also uses the method riwayat bi al-lafẓī. In contrast, the approach used by Ihsan al-Jampasi is the usage of various sighat (format) to deliver the hadith. This includes stating the source of the hadith and at times using the method riwayat bi al-ma‘na.